Sister M. Madeleva Wolff, CSC - Petit, OP, M. Loretta (Catholic Education: A Journal of Inquiry and Practice, 2006)
Sister M. Madeleva Wolff, C.S.C., teacher, essayist, poet, and college administrator, through her creative ability and innovative practices made possible major contributions to Catholic education in her lifetime. Without her strong personality and boundless energy, many of her dreams for an ideal college curriculum would not have come to fruition. Her most significant legacy, the Graduate School of Theology, afforded for the first time the opportunity for the laity and religious women to study theology at the graduate level. She served as president of St. Mary’s College, Notre Dame, Indiana, from 1934 to 1961.